Roles of female leaders of educational in Vietnam National University - Huy, Nguyen Duc; Chung, Nguyen Huu; Kien, Nguyen Trung (VNU Journal of Science: Education Research, 2017)
In order to understanding the increasing number of women leaders in Vietnamese higher education. The research was a qualitative study using a narrative inquiry research design as a means to elicit the lived experience of some respected female educational leaders. However, a higher of males leader than females still fills senior management roles in Vietnamese higher education.  This study explores of perspective the leadership styles of women leaders who want to positions of leadership in higher education. Most of the female leaders have not leadership training at any school, so their leadership and management by experiences.The identification of important factors effect on the educational leadership of these figures will provide insight into the nature of leadership in relation to teaching and learning in Vietnamese higher education. Research will focus on interview as method for exploring thestories offemale educational leaders in Vietnam National University, Hanoi (VNU). The role of female leaders in changing, developing and perfecting valuable structures. Exploring these stories will demonstrate and can be understood the leadership styles of female leader in at VNU.